Exploring the Dynamics of Managerial Accounting Practices: A Literature Review - Sulisnaningrum, Ema (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This research conducts a qualitative analysis to explore the dynamics of managerial accounting practices, aiming to uncover determinants of adoption, impacts on organizational performance, and contextual factors shaping such practices. The study employs a systematic literature review methodology, synthesizing existing research from academic databases and journals. Through thematic analysis, key themes including organizational determinants, impacts on performance, and contextual influences are identified and analyzed. The findings reveal that organizational factors such as size, structure, culture, and leadership style significantly influence the adoption of advanced managerial accounting techniques. Additionally, external factors such as regulatory requirements, industry dynamics, and technological advancements play a crucial role in shaping adoption patterns. Effective implementation of managerial accounting practices is associated with improved financial performance, operational efficiency, and strategic decision-making capabilities. Furthermore, contextual factors including industry dynamics, environmental uncertainty, and technological advancements influence managerial accounting practices, driving organizations to adopt innovative and agile approaches. The study contributes to advancing scholarly understanding of managerial accounting practices and highlights avenues for future research.